Feminism : perspectives, stereotypes/misperceptions and social implications - Stroud, Pearce ([Hauppauge], New York : Nova Science Publishers, 2014)
In this book the authors present current research in the study of feminism. Topics discussed in this compilation include the feminist focus on women and substance abuse treatment; the question of whether or not purely female societies can truly exist; women in elite positions within medicine; black women and their situation of discrimination and vulnerability in Brazil; the impact of migration on the reconfiguration of family dynamics; feminism and difference; theorizing African feminism; gender stereotypes and the effect on women's persistence in STEM fields; and an antidote for global femini.
Ch. 1 Linking Past to Present: Forecasting the Feminist Focus on Women and Substance Abuse Treatment / Jolene M. Sanders -- ch. 2 Are Permanent, Purely Female, Societies Possible? / Jacques Hanoune -- ch. 3 Room at the Top ... or Not? Women in Elite Positions within Medicine / Trudie E. Roberts -- ch. 4 Black Women and Their Situation of Discrimination and Vulnerability in Brazil / Sonia Beatriz dos Santos -- ch. 5 Examining the Impact of Migration on the Reconfiguration of Family Dynamics: The Experiences of Haitian Immigrant Women in Canada / Louise Racine -- ch. 6 Feminism and Difference: A Pathway to Women's Reconstruction / Maria J. Binetti -- ch. 7 Theorizing African Feminism / George Odhiambo -- ch. 8 How Do Gender Stereotypes Affect Women's Persistence in STEM Fields? / Roxanne M. Hughes -- ch. 9 Antidote for Global Feminist Gaps As Encoded in Sindiwe Magona's Black South African Autobiographies / Lesibana Rafapa.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Master record variable field(s) change: 050, 082
Keywords: Feminism; Feminist theory; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Feminism; Feminist theory; Electronic books